Re-Expression of Tafazzin Isoforms in TAZ-Deficient C6 Glioma Cells Restores Cardiolipin Composition but Not Proliferation Rate and Alterations in Gene Expression - Jagirdar, Gayatri; Elsner, Matthias; Scharf, Christian; Simm, Stefan; Borucki, Katrin; Peter, Daniela; Lalk, Michael; Methling, Karen; Linnebacher, Michael; Krohn, Mathias; Wolke, Carmen; Lendeckel, Uwe (Frontiers in Genetics, 2022)
Tafazzin - an acyltransferase - is involved in cardiolipin (CL) remodeling. CL is associated with mitochondrial function, structure and more recently with cell proliferation. Various tafazzin isoforms exist in humans. The role of these isoforms in cardiolipin remodeling is unknown. Aim of this study was to investigate if specific isoforms like Δ5 can restore the wild type phenotype with respect to CL composition, cellular proliferation and gene expression profile.In addition, we aimed to determine the molecular mechanism by which tafazzin can modulate gene expression by applying promoter analysis and (Ingenuity Pathway Analyis) IPA to genes regulated by TAZ-deficiency. Expression of Δ5 and rat full length TAZ in C6-TAZ- cells could fully restore CL composition and – as proven for 5 – this is naturally associated with restoration of mitochondrial respiration. A similar restoration of CL-composition could not be observed after re-expression of an enzymatically dead full-length rat TAZ (H69L; TAZMut). Re-expression of only rat full length TAZ could restore proliferation rate. Surprisingly, the Δ5 variant failed to restore wild-type proliferation. Further, as expected, re-expression of the TAZMut variant completely failed to reverse the gene expression changes, whereas re-expression of the TAZ-FL variant largely did so and the Δ5 variant to somewhat less extent. Very likely TAZ-deficiency provokes substantial long-lasting changes in cellular lipid metabolism which contribute to changes in proliferation and gene expression, and are not or only very slowly reversible.